Selective Laser Trabeculoplasty versus Topical Anti-Glaucoma Medications in the Treatment of Patients with Primary Open-Angle Glaucoma (Journal of Pharmaceutical Negative Results, 2023)
Purpose: This study aims to report and compare the percent of eyes with positive responses in the group treated by SLT (IOP falls in the normal range with a cessation or decrease in the number of anti-glaucoma drugs).Patients and Methods: In the trial, 86 eyes from 51 patients with OAG were enrolled; the recruited sample was divided evenly between the case and control study arms, each of which contained 43 eyes (a treatment group and a control group), as follows: Group I (intervention group): 43 Patients who received SLT as primary or adjunctive therapy, included patients with newly diagnosed POAG, patients who want to decrease medical glaucoma treatment, and patients diagnosed with POAG currently on medical treatment, either intolerant of medical treatment or not well controlled to the target level. Group II (control group): 43 Patients had running on anti-glaucoma treatment. In this study, SLT was performed in the intervention group (group I), and the results were compared to the control group (group II).Results: SLT significantly reduced the amount of anti-glaucoma medication required while maintaining adequate control, (full replacement) in 23 eyes (53.5%). Partial replacement (reduction in drugs) was achieved in all other cases. The mean number of glaucoma molecules after SLT decreased from 1.79 ± 1.30 after 1 year to 0.63 ± 0.79 with a statistically significant difference all over the follow-up time (p < 0.001). According to our findings, SLT is a better method for replacing or reducing the number of glaucoma medications without serious complications occurring for the duration of the study.Conclusion: SLT is effective as primary or adjunctive therapy for the replacement treatment of POAG.